Knowledge and Practices Regarding Polycystic Ovary Syndrome among Physicians in Europe, North America, and Internationally: An Online Questionnaire-Based Study - Gibson-Helm, Melanie; Dokras, Anuja; Karro, Helle; Piltonen, Terhi; Teede, Helena J. (Seminars in Reproductive Medicine, 2018)
Background To inform knowledge translation by identifying evidence–practice gaps in polycystic ovary syndrome (PCOS) care and variations between disciplines and across world regions via an online, anonymous, devised questionnaire distributed via professional societies and completed by 1,495 physicians (2015–2016).Methods Multivariable logistic regression analyses generated adjusted odds ratios (OR) and 95% confidence intervals (CI) for associations between outcome measures and world region, specialty, annual patients with PCOS, age, and sex.Results Features corresponding to Rotterdam diagnostic criteria were well recognized (e.g., irregular menstrual cycles by 99% of physicians), but psychological implications were recognized only by 29 to 64%. Reproductive endocrinologists were more likely to use Rotterdam diagnostic criteria (OR: 3.1; 95% CI: 2.3–4.3; p < 0.007) than obstetrician-gynecologists. Reproductive (OR: 2.0; 95% CI: 1.5–2.8; p < 0.007) and medical endocrinologists (OR: 3.1; 95% CI: 1.7–5.7; p < 0.007) were more likely to recommend lifestyle management than obstetrician-gynecologists. Physicians in Europe (OR: 4.7; 95% CI: 3.5–6.1; p < 0.007) and other regions (OR: 4.0; 95% CI: 2.8–5.9; p < 0.007) were more likely to use Rotterdam diagnostic criteria than physicians in North America.Conclusion Knowledge gaps in PCOS care to be addressed internationally include physician awareness of the breadth of PCOS features, application of diagnostic criteria, and recommending lifestyle management effectively.
Keywords: polycystic ovary syndrome; professional practice gaps; professional education; endocrinologists; gynecologists